Notes on Early Land Plants Today. 25. Lejeunea soae, a new name for Lejeunea chinensis, hom. illeg. (Lejeuneaceae, Marchantiophyta) - Zhu, Rui-Liang; Wei, Yu-Mei; Söderström, Lars; Hagborg, Anders; Konrat, Matt Von (Phytotaxa, 2013)
Zhu & So (1999) transferred Trachylejeunea chinensis to Lejeunea Libert (1820: 320). Unfortunately this is a later homonym of Lejeunea chinensis (Steph.) Steph. ex Kashyap, which now is Tuzibeanthus chinensis. Lejeunea chinensis (Herzog) R.L.Zhu & M.L.So nom. illeg. is a good species which is well characterized and readily separated from other Lejeunea species by the 1) ovate, convex leaves with an arched dorsal margin, 2) male bracteoles present throughout the androecium, 3) large and imbricate underleaves, 4) large, strongly inflated leaf lobule with a square or rectangular apical tooth, and 5) finely punctuate leaf cuticle. Thus a new name is needed.